Case report: A rare case of death due to end-stage renal disease caused by Tripterygium wilfordii-induced myelosuppression - Zhang, Wen; Liu, Xinyin; Xia, Cong; He, Lingzhi; Ma, Hongzhen; Wang, Xiaoran; Zhang, Peipei (Frontiers in Medicine, 2022)
Tripterygium wilfordii—a traditional Chinese herbal medicine—is used to treat several diseases, including chronic kidney disease, rheumatic autoimmune disorder, and skin disorders. With the development of modern pharmacology, scientists have gradually realized that T. wilfordii has side effects on several organs and systems of the human body, including the liver, kidney, reproductive system, hematopoietic system, and immune system. Our understanding of its toxicity remains unclear. The incidence of problems in the hematopoietic system is not low but few related studies have been conducted. The serious consequences need to be of concern to clinicians and scientists. To ensure the safety of patients, it is important to elucidate the mechanism underlying the damage to the hematopoietic system caused by T. wilfordii and strategies to reduce its toxicity. Routine blood and biochemical tests should be conducted when administering T. wilfordii, and in case of any abnormality, the medication should be terminated in time along with a comprehensive symptomatic treatment. Herein, we report the case of a 50-year-old Chinese female with end-stage renal disease (ESRD) who developed severe bone marrow suppression after taking a short-term normal dose of a T. wilfordii-containing decoction. She died of sepsis and septic shock, although timely therapeutic measures (e.g., stimulating hematopoiesis, anti-infection treatment, and hemodialysis) were administered. To the best of our knowledge, this is the first report of death by T. wilfordii-induced myelosuppression from a short term, conventional dose in an adult female with ESRD. Although the underlying mechanism remains unclear, this case contradicts the notion that side effects on the hematopoietic system are nonlethal.